Extended Feedback Linearization Control for Voltage Regulation in a Buck Converter with an Unknown Resistive Load (2023)
This paper deals with the control problem in a buck converter while considering an unknown resistive load. The control design is based on extended feedback linearization (EFL) theory, which allows finding a general control law equivalent to the approximated feedback control method when the state variables are at the desired equilibrium point. The main advantage of an EFL controller is that the final feedback gains are independent of the converter parameters if and only if all the capacitances and inductances of the converter are perfectly known. To define the resistive load value, the inverse and invariance estimation method was employed, aiming to ensure the exponential convergence of the real resistive value. Numerical comparisons with an integral-action, passivity-based control design demonstrate the effectiveness of the proposed EFL approach. All numerical simulations were conducted in the PLECs simulation tool of the MATLAB/Simulink environment. © 2023 IEEE